Heavy metals concentration in undisturbed peat soil at Pekan District, Pahang, West Malaysia - Abdul, Wahab; Muzamir, Hasan; Ud Din, Zaheer; Zaman, Qamar Uz (School of Renewable Energy, Maejo University, 2021)
Soil is a mixture of various materials such as air, water, and organic matter. Soft soil (peat) has very deprived physical properties such as low shear strength, high moisture content, high compressibility, and permeability. In an engineering perspective it is considered as a weak soil, while an the agricultural context it is considered as a rich soil because of high amount of carbon. Heavy metals such as arsenic, chromium, cadmium, and lead are considered highly toxic, and it may produce mutagenic, carcinogenic, and genotoxic effects. This study examined the heavy metals concentration of peat soil. There were nine peat samples collected from three different sites which are Kampung Bahru (KB), Kampung Lancang I (KL I), and Kampung Lancang II (KL II), Pekan district, Pahang State, Malaysia. This research indicated that the average organic content were 97.8 % for KB, 95.88 % for KL I, and 98.48 % for KL II approximately for peat soil. It concluded that the concentration of As, Cu, Ni, Pb, and Zn exceeded the standard guidelines, and Mg concentration was observed below the recommended guidelines. It is essential to extract these metals and further assess their toxicological impact on the environment and human health.